Analysis of knowledge flows in a construction project using a social network analysis tool - Ibrahim, Rahinah (2005)
Construction researchers have difficulty standardizing the workflow of construction projects while organization researchers cannot fit the complex development workflow processes with the established Galbraith’s information processing design. Aware that the possession of knowledge within a construction team cannot guarantee its movement among the team members, this problem becomes critical when a multi-disciplinary team handling a global project needs to sustain its cost and schedule in ensuring its successful completion. Therefore, prior to developing a flexible yet dynamic knowledge management system for the construction industry, we need to ascertain if the industry’s knowledge flows conform to current Wegner’s transactive memory theory. This paper describes an example how we can utilize a social network analysis tool and methodology to analyze knowledge flows of an affordable housing project. The study tested the conformance, and found that knowledge flows in functional knowledge areas support transactive memory theory, but not in tacit knowledge areas. This paper encourages multi-disciplinary collaboration to solve engineering problems.